2018
DOI: 10.1155/2018/9643721
|View full text |Cite
|
Sign up to set email alerts
|

Alginate/Hydroxyapatite-Based Nanocomposite Scaffolds for Bone Tissue Engineering Improve Dental Pulp Biomineralization and Differentiation

Abstract: Tissue engineering is widely recognized as a promising approach for bone repair and reconstruction. Several attempts have been made to achieve materials that must be compatible, osteoconductive, and osteointegrative and have mechanical strength to provide a structural support. Composite scaffolds consisting in biodegradable natural polymers are very promising constructs. Hydroxyapatite (HAp) can support alginate as inorganic reinforcement and osteoconductive component of alginate/HAp composite scaffolds. There… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
54
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(65 citation statements)
references
References 43 publications
8
54
0
1
Order By: Relevance
“…The results showed that nanofiber scaffolds containing both DXM and rhBMP2 drugs could synergistically induce the upregulation of ALP activity in rBMSCs and had better bone induction ability. Alizarin red reacts with calcium to produce a dark red compound, which stains the calcium nodules deposited [28]. Therefore, ARS was further used to characterized the degree of differentiation.…”
Section: Mechanical Performancementioning
confidence: 99%
“…The results showed that nanofiber scaffolds containing both DXM and rhBMP2 drugs could synergistically induce the upregulation of ALP activity in rBMSCs and had better bone induction ability. Alizarin red reacts with calcium to produce a dark red compound, which stains the calcium nodules deposited [28]. Therefore, ARS was further used to characterized the degree of differentiation.…”
Section: Mechanical Performancementioning
confidence: 99%
“…However, alginate exhibits some limitations in the regard of prospective bone tissue applications, such as the absence of sites for cell attachment or specific receptor interactions, which limits its long-term functionality, further impaired by the swelling-disintegration-erosion of these hydrogels' upon implantation, week biomechanical properties, poor bioresorbability and bioactivity [10][11][12][13]. Therefore, the use of nanohydroxyapatite (nanoHA) as a reinforcing component with osteocondutive capabilities can contribute to overcome some of these potential limitations [4,14]. NanoHA is commonly used in bone tissue regeneration due to its chemical similarity to the inorganic component of the bone matrix and its inherent characteristics such as biocompatibility, osteoinduction, osteocondutive and osteointegration [4,15,16].…”
Section: Introductionmentioning
confidence: 99%
“…NanoHA is commonly used in bone tissue regeneration due to its chemical similarity to the inorganic component of the bone matrix and its inherent characteristics such as biocompatibility, osteoinduction, osteocondutive and osteointegration [4,15,16]. Although in some studies nanoHA was already used to reinforce Alg matrixes [14,[17][18][19][20], no studies have yet addressed the systematic influence of nanoHA on alginate-based hydrogel systems, neither the effect of distinct nanoHA amounts on its physic-chemical properties and biological response. This is of the utmost relevance, since the amount of nanoHA within the composition of polymer-based hydrogels is crucial to design an efficient composite for bone tissue regeneration.…”
Section: Introductionmentioning
confidence: 99%
“…The aim of BTE is not only to provide 3D structutres and cell proliferation without cell cytotoxicity or foreign body reaction but also the regeneration of new bone by provoking osteogenic differentiation of stem cells (4,61).…”
Section: Discussionmentioning
confidence: 99%